Caracterização de um fragmento de caatinga em Sergipe : produção de forragem e comportamento ingestivo de caprinos - Mendonça, Leomax Mendes (2017)
The caatinga is formed by a great variety of native species, mostly forage use, which almost always has been used without any environmental control technique or even with no perspective of optimizing livestock from a rational management. The objective of this work was to assess the availability of dry matter (DM), as well as the ingestive behavior of goats in a caatinga fragment in the semi-arid Sergipano, from August 2016 to June 2017. To estimate the production of Dry matter and chemical analysis of fodder, 30 points with equidistant coordinates were used, the same ones marked with the aid of a GPS. At each point an area of 4m2 was delimited and all species (arboreal, shrub and herbaceous) were collected. To evaluate the ingestive behavior, six goats (SRD) were used, with a mean live weight of 20 kg and a mean age of 1.5 years, in a caatinga area of 4.6ha. Data collection was done once a month during the experimental period, making a total of 6 hours of each observed day, where the behavioral variables were recorded: eating, ruminating, leisure, drinking water, walking and social interaction. For each animal, an observer was chosen who, through the focal method (recording of data every 5 minutes) was monitored from the beginning to the end of the experiment. It was observed that the macambira, litter and herbaceous stratum were the main forage resources in the animals' diet (p <0.05), and the litter was present in most of the DM production of the area / ha during the experimental period. In relation to the ingestive behavior, it was observed that the leisure and eating activities varied during the experiment (p <0.05) and this is directly influenced by the season and the availability of iv the existing fodder resource in the experimental area. The studied caatinga area presents a need for strategic management that favors the presence of fodder plants so that the variations in the supply and quality of the forage seek the sustainability of the cattle raising in this area.